Capital's Grabbing Hand? A Cross-Country/Cross-Industry Analysis of the Decline of the Labour Share - Bassanini, Andrea (OECD Publishing, 2012)
We examine the determinants of the within-industry decline of the labour share, using industry-level annual data for 25 OECD countries, 20 business-sector industries and covering up to 28 years. We find that total factor productivity growth - which captures (albeit imprecisely) capital-augmenting or labour-replacing technical change - and capital deepening jointly account for as much as 80% of the within-industry contraction of the labour share. We also find that other important factors are privatisation of state-owned enterprises and the increase in international competition as well as off-shoring of intermediate stages of the production process. By contrast, we are unable to detect any effect from increases in domestic competition brought about by entry deregulation
Keywords: Employment; Social Issues/Migration/Health